Workplace learning during organizational onboarding: integrating formal, informal, and self-regulated workplace learning - Mitschelen, Annabell; Kauffeld, Simone (Frontiers in Organizational Psychology, 2025)
IntroductionIn knowledge-based work environments, workplace learning is essential for successful employee integration and long-term performance. Onboarding represents a crucial phase in which newcomers begin to acquire organizational knowledge, take on new tasks, and establish social connections. While existing research has highlighted the role of formal and informal learning formats, less is known about how different learning forms interact and how newcomers actively contribute to their onboarding by engaging in self-regulated learning behaviors.MethodsThis qualitative study investigates onboarding as a dynamic learning process, focusing on how newcomers engage in formal, informal, and self-regulated workplace learning behaviors across four content dimensions: compliance, clarification, connection, and culture. The study is based on 40 semi-structured interviews with newcomers and analyzed using qualitative content analysis.ResultsThe findings show that newcomers engage in diverse learning activities that vary in structure and learner involvement. These differences illustrate distinct patterns in observed workplace learning behaviors across the four content dimensions.DiscussionThe study contributes to onboarding and workplace learning theory by linking content dimensions to learning forms and highlighting how newcomers actively shape their onboarding experience. It challenges static models of onboarding and conceptualizes it instead as an individualized and interactive learning path shaped by both organizational structures and learner behavior. Practical implications include designing onboarding processes that combine structure with learner autonomy and recognize newcomers not only as recipients of information, but as active participants who can co-construct organizational learning through their engagement.